Hydrometallurgical Treatment of Spent Lithium-Ion Batteries: A study of optimal conditions for the leaching - Wendy, Zhou (My University, 2018)
The interest of recycling lithium-ion batteries to recover valuable metals has traditionally been focused on economic benefit. Nowadays, the interest has shifted towards a more global perspective on waste disposal because of issues from both environmental impacts and resource supply. The current recycling processes are designed to operate with small lithium-ion batteries from portable electronic devices [1], and do not satisfy the new requirement in environment and recycling efficiency for larger, more advanced lithium-ion batteries from electric vehicles and plug-in hybrid electric vehicles. Therefore, recycling processes must be developed to accommodate an increasing amount of vehicle lithium-ion batteries, that are expected to enter the waste stream in the near future. Leaching is an essential step for effective recovery of metals from spent lithium-ion batteries during hydrometallurgical treatment. The objective of the present work was to determine the optimal leaching conditions for recovery of metals from spent lithium-ion batteries. The leaching was carried out by using hydrochloric acid. Effects of different concentrations, temperatures, reaction times and solid-to-liquid ratios were examined. With optimal leaching conditions found to be 1 M hydrochloric acid, 60 min leaching time, at 40oC with solid to liquid ratio of 1/20 g/ml.
Keywords: Kemi; Kemiteknik; Chemical Sciences; Chemical Engineering